The age of federalism - Elkins, Stanley M.; McKitrick, Eric L. (New York Oxford University Press, 1993)
When Thomas Jefferson took the oath of office for the presidency in 1801, the United States had just passed through twelve critical years, years dominated by some of the towering figures of our history and by the challenge of having to do everything for the first time. Washington, Hamilton, Madison, Adams, and Jefferson himself each had a share in setting the nation's important precedents, in organizing the public finances, and in attempting - though with minimal success - to compel respect for the American republic from the powers of Europe. The historical era bounded by those first years is brilliantly represented in The Age of Federalism. Written by esteemed historians Stanley Elkins and Eric McKitrick, The Age of Federalism gives us a reflective, deeply informed analytical survey of this extraordinary period. Ranging over the widest variety of concerns - political, cultural, economic, diplomatic, military - the authors keep in view not only the problems the new nation faced but also the particular individuals who tried, with mixed results, to solve them. They intersperse their account with subtly perceptive (and sometimes delightful) character sketches, not only of the great central figures - Washington and Jefferson, Talleyrand and Napoleon Bonaparte - but also of various lesser ones, such as George Hammond, Britain's frustrated minister to the United States, James McHenry, Adams's hapless Secretary of War, a pre-Chief Justice version of John Marshall, and others. They weave these lively profiles into an analysis of the major controversies of the time in an effort to recover something that is now two centuries out of reach, the psychology of a generation of nation-builders, not all of it attractive. The moral urgency of these issues, and the bitterness of the disagreements over them, reflected a fearful sense that the entire future hung on the particular way any one of them was settled. We thus see, for example, how the fight over Hamilton's Treasury system widened an ideological gulf between Hamilton and the Virginians, Madison and Jefferson, that became unbridgeable; how their divisions came to involve questions of foreign relations as well as domestic policy; and how the passions thus generated led to what everyone professed to deplore, the formation of political parties. The most complex issues and episodes are presented with a clarity and a connectedness that they have seldom had in previous treatments. We get a fresh reading of the Whiskey Rebellion of 1794, the Adams presidency, the XYZ Affair, the naval Quasi-War with France, and the desperate Federalist maneuvers in 1800, first to prevent the reelection of Adams and then to nullify the election of Jefferson. The statesmen of the founding generation, the authors concede, did "a surprising number of things right." Some things, however, went resoundingly wrong: the hopelessly underfinanced effort to construct a capital city on the Potomac (it would have made far more sense, the authors argue, to leave it in New York); the drive in 1798 to form a mighty army that virtually nobody wanted; and prosecutions under the Alien and Sedition Acts which turned into a comic nightmare. The Age of Federalism is the fruit of many years of study and discussion. It combines breadth of scholarship with those touches already familiar in the authors' previous handling of historical subjects: analogies, fascinating side-excursions, counterfactual projections, and understated irony, all couched in a prose that is graceful and lucid. With it, Stanley Elkins and Eric McKitrick have produced a comprehensive synthesis, long awaited by historians, of our early national era.
Includes bibliographical references (pages 757-909) and index.
Keywords: United States -- Politics and government -- 1789-1809.